Evaluation of amidoxime derivatives as prodrug candidates of potent bis-cationic antimalarials. Issue 16 (15th August 2019) - Berger, Olivier; Ortial, Stéphanie; Wein, Sharon; Denoyelle, Séverine; Bressolle, Françoise; Durand, Thierry; Escale, Roger; Vial, Henri J.; Vo-Hoang, Yen
Graphical abstract: Abstract: Plasmodium falciparum is responsible for most of the cases of malaria and its resistance to established antimalarial drugs is a major issue. Thus, new chemotherapies are needed to fight the emerging multi-drug resistance of P. falciparum malaria, like choline analogues targeting plasmodial phospholipidic metabolism. Here we describe the synthesis of amidoxime derivatives as prodrug candidates of reverse-benzamidines and hybrid compounds able to mimic choline, as well as the design of a new series of asymmetrical bis-cationic compounds. Bioconversion studies were conducted on amidoximes in asymmetrical series and showed that amidoxime prodrug strategy could be applied on C -alkylamidine moieties, like benzamidines and that N -substituents did not alter the bioconversion of amidoximes. The antimalarial activity of the three series of compounds was evaluated in vitro against P. falciparum and in vivo against P. vinckei petteri in mice.